Rewiring bacterial two-component systems by modular DNA-binding domain swapping - Schmidl, Sebastian R.; Ekness, Felix; Sofjan, Katri; Daeffler, Kristina N.-M.; Brink, Kathryn R.; Landry, Brian P.; Gerhardt, Karl P.; Dyulgyarov, Nikola; Sheth, Ravi U.; Tabor, Jeffrey J. (Nature chemical biology, 2019)
Two-component systems (TCSs) are the largest family of multi-step signal transduction pathways and valuable sensors for synthetic biology. However, most TCSs remain uncharacterized or difficult to harness for applications. Major challenges are that many TCS output promoters are unknown, subject to cross-regulation, or silent in heterologous hosts. Here, we demonstrate that the two largest families of response regulator DNA-binding domains can be interchanged with remarkable flexibility, enabling the corresponding TCSs to be rewired to synthetic output promoters. We exploit this plasticity to eliminate cross-regulation, un-silence a gram-negative TCS in a gram-positive host, and engineer a system with over 1,300-fold activation. Finally, we apply DNA-binding domain swapping to screen uncharacterized Shewanella oneidensis TCSs in Escherichia coli , leading to the discovery of a previously uncharacterized pH sensor. This work should accelerate fundamental TCS studies and enable the engineering of a large family of genetically encoded sensors with diverse applications. Rewiring of bacterial two-component systems (TCSs) was achieved by DNA-binding domain swapping of the two largest response regulator families, which enables cross-species porting and provides a tool for identifying ligands for uncharacterized TCSs.